2015
DOI: 10.18632/oncotarget.3592
|View full text |Cite
|
Sign up to set email alerts
|

Activation of hypoxia signaling induces phenotypic transformation of glioma cells: implications for bevacizumab antiangiogenic therapy

Abstract: Glioblastoma (GBM) is the most common and deadly primary brain tumor in adults. Bevacizumab, a humanized monoclonal antibody against vascular endothelial growth factor (VEGF), can attenuate tumor-associated edema and improve patient symptoms but based on magnetic resonance imaging, is associated with non-enhancing tumor progression and possibly gliosarcoma differentiation. To gain insight into these findings, we investigated the role of hypoxia and epithelial-mesenchymal transition (EMT)-associated proteins in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
77
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 47 publications
2
77
0
Order By: Relevance
“…One of these factors is hypoxia. 28,29 Several studies have demonstrated that prolonged anti-angiogenic therapy increased the expression of mesenchymal phenotypes, [30][31][32][33] and this may be due to hypoxia induced by excessive anti-angiogenesis. Other studies have also shown that hypoxia and hypoxia-inducible factor-1 alpha (HIF-1α) promote EMT in several tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…One of these factors is hypoxia. 28,29 Several studies have demonstrated that prolonged anti-angiogenic therapy increased the expression of mesenchymal phenotypes, [30][31][32][33] and this may be due to hypoxia induced by excessive anti-angiogenesis. Other studies have also shown that hypoxia and hypoxia-inducible factor-1 alpha (HIF-1α) promote EMT in several tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…4 These treatment-related effects may in part be explained by intratumoral hypoxia resulting from BEV-induced vessel pruning and subsequent activation of compensatory survival pathways that would be expected to negatively impact BEV response by negating any early transient benefits attributable to reductions in vascular permeability and contrast enhancing tumor. 3 Indeed, the effects of antiangiogenic agents on tumor oxygenation status remain controversial, with evidence supporting either vascular regression, which is associated with increased intratumoral hypoxia, 5,6 or a so-called ''normalization'' of the tumor vasculature, resulting in improved tumor oxygenation and cytotoxic chemotherapy sensitivity. [7][8][9] The tumor microcirculation is characterized by abnormal capillary bed topology, elevated edema pressure, and microthromboses, all of which give rise to shunting of oxygenated blood through the tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Glioblastoma has strong activity of migration and invasion [2], which is associated to low oxygen condition of tumor microenvironment [4][5][6]. Thus it's essential to find a way to block hypoxia-induced migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…This aggressive phenotype is possibly relevant to hypoxia, which is one of the most remarkably characteristics of glioma microenvironment and might play a crucial role in glioma growth, development, and angiogenesis [3]. It has been documented that hypoxia also induces migration and invasion of glioma cells [4][5][6], which involves a series of transduction pathways and signal molecules.…”
mentioning
confidence: 99%